2019
DOI: 10.1590/rbz4820190074
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality of rabbits fed Tithonia tubaeformis weed

Abstract: Non-ruminantsFull-length research article Carcass and meat quality of rabbits fed Tithonia tubaeformis weed ABSTRACT -The objective of this study was to use different parts of the Tithonia tubaeformis plant in feed for fattening rabbits and then observe the effects on carcass and meat quality. Forty-eight weaned rabbits (35 days of age) were randomly assigned to four groups (n = 12 by treatment). Animals were fed ad libitum a control diet as well as three experimental diets, with addition of Tithonia tubaeform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(41 reference statements)
2
2
0
2
Order By: Relevance
“…pH values determined in this study did not change in result by feeding rabbits with amaranth oilcake which is in agreement with data by Molina et al (2018),Manciniet al (2018; however, in other studies reported of increase in meat рН for rabbits that were fed with natural plant fodder additives (Cullereet al, 2016;Zepeda-Bastida et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…pH values determined in this study did not change in result by feeding rabbits with amaranth oilcake which is in agreement with data by Molina et al (2018),Manciniet al (2018; however, in other studies reported of increase in meat рН for rabbits that were fed with natural plant fodder additives (Cullereet al, 2016;Zepeda-Bastida et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Ibrahim et al (2011), using 0.75% ginger in rabbit feed, andMancini et al (2018), using 4 g and 8 g of ginger in the diet, reported no effects of ginger treatment on carcass quality. Although several other plants have been used in rabbit feed in previous studies, in general, no effects on carcass quality have been found Zepeda-Bastida et al (2019). found that Tithonia tubaeformis in rabbit feed increased kidney size relative to that of controls; similarly, we found that dietary ginger increased kidney size Ayala-Martínez et al (2020).…”
supporting
confidence: 55%
“…Various medicinal plants have been investigated as potential dietary sources of bioactive compounds with antioxidant or antimicrobial activity or as nutritional additives or supplements (Zeng et al, 2015;Dalle Zotte et al, 2016). These plants include ginger (Bhandari et al, 1988;Ibrahim et al, 2011;Mancini et al, 2018;Abdel-Gabbar et al, 2019), epazote (García-Vázquez et al, 2020), Tithonia tubaeformis (Zepeda-Bastida et al, 2019), bilberry pomace (Dabbou et al, 2017), oregano, rosemary (which contains vitamin E; Cardinali et al, 2015), onion, bilberry, and strawberry and their extracts (Kone et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit production is a potential solution to the meat deficiency problem of meat deficiency due to its unique characteristics as a prolific and highly nutritious animal with low cholesterol content of meat [1], which requires working on increasing their production without harmful effects on them. [2] indicated that scientists are now occupied by introducing unconventional natural feed supplements into diets of livestock, which can play an important role in improving animal and chicken production and health.…”
Section: Introductionmentioning
confidence: 99%